Media Sosial Sebagai Alat Tindak Pidana Makar - Vicky Yuliana Saputri (Faculty of Law, Universitas Airlangga, 2021)
AbstractIn Indonesia, the replacement of the President is regulated in article 6A of the 1945 Constitution, if this provision is violated it will result in an unlawful act. Not only this article but also contained in article 7A of the 1945 Constitution. Technology at this time has experienced a very large development, social media is used by the public to convey information. Lately, many phenomena in the form of dismissal and the desire to assassinate the president have been carried out in cyberspace. Then what is the criminal responsibility for acts committed using social media. Considering that a criminal act if the act is committed or only an act of planning can have fatal consequences, and the treason articles can be applied, namely article 104, article 106 and article 107 of the Criminal Code.Keywords: Criminal Act of treason; Social Media; Criminal Liability.AbstrakDi Indonesia dalam penggantian Presiden diatur dalam pasal 6A Undang-Undang Dasar 1945, jika ketentuan tersebut dilanggar maka akan mengakibatkan perbuatan melawan hukum. Tidak hanya pasal tersebut namun juga terdapat dalam pasal 7A Undang-Undang Dasar 1945.Teknologi pada masa saat ini mengalami perkembangan yang sangat besar, media sosial digunakan masyarakat untuk menyampaikan informasi. Belakangan ini banyak sekali fenomena berupa pemberhentian dan keinginan untuk membunuh presiden dilakukan di dunia maya. Lalu bagaimana pertanggungjawaban pidana atas perbuatan yang dilakukan menggunakan media sosial tersebut. Mengingat tindak pidana bila perbuatan itu dilakukan atau hanya perbuatan perencanaan dapat berakibat fatal, dan dapat diberlakukan pasal-pasal makar yaitu pasal 104, pasal 106 dan pasal 107. Kata Kunci: Tindak Pidana Makar; Media Sosial; Pertanggungjawaban Pidana.